KARAKTERISTIK PERMEN JELLY TIMUN SURI (Cucumis melo L.) DENGAN PENAMBAHAN SORBITOL DAN EKSTRAK KUNYIT (Curcuma domestika Val.) - Merynda Indriyani Syafutri; Eka Lidiasari; Hendra Indawan (Food and Nutrition Society of Indonesia, 2010)
The objective of this research was to determine the chemical and organoleptic characteristics of Cucumis melo L. jelly candies with the addition of sorbitol and Curcuma domestika Val. extract. This research was conducted in the Chemical Laboratory of Agricultural, Department of Agricultural Technology, Agricultural Faculty, Sriwijaya University, Indralaya, from January 2010 to June 2010.This research used a Factorial Completely Randomized Design with two treatments and three replications for each treatment. S factor was the addition of sorbitol concentration (9%, 16% and 23%) and E was the concentration factor addition of Curcuma domestika Val. extract (5%, 7% and 9%). The results showed that the addition of sorbitol concentration had significant effect on the water content, pH, total sugar and antioxidant activity of Cucumis melo L. jelly candies. The addition of Curcuma domestika Val. extract had significant effect on the water content and antioxidant activity of Cucumis melo L. jelly candies. Interaction addition of sorbitol and Curcuma domestika Val. extract had significant effect on the antioxidant activity of jelly candies.S2E2 treatment (sorbitol 20% and 7.5% Curcuma domestika Val. extract) was the best treatment with chemical characteristics (water content 36.48%, ash content 3.01%, pH 5.03, total sugar 37.00% and the antioxidant activity 27.09%), and sensory characteristics by scoring preferences (color 3.08, texture 2.88, odour 3.08 and taste 2.88).